ENCONTRAR LA POBLACIÓN DE LAS PLANTAS DE BANANO WILLIAMS CULTIVADAS EN UN SISTEMA DE CÍRCULO QUE PERMITA LA MAYOR PRODUCCIÓN EN LA EET PICHILINGUE - Peñafiel Ramos, Elian Eduardo (2023)
The investigative work was carried out in the “La Pavera” lot, near the Pichilingue Tropical Experimental Station and consisted of finding the appropriate population for optimal production, in a crop circle system planted with bananas at high densities. 7 treatments were evaluated in the study: Hexagon (1944 plant/ha), Heptagon (2268 plant/ha), Octagon (2592 plant/ha), Nonagon (2916 plant/ha), Decagon (3240 plant/ha), Undecagon (3564 plant/ha), and Dodecagon (3888 plant/ha), arranged in a DBCA with four repetitions. The variables evaluated were: height (m), diameter (cm) of the pseudo stem, number of leaves, caliber, length (mm / cm) of the fruit, number of hands and fingers and weight of the bunch (kg).